Aplicação de Kaizen em um setor de manufatura fabril - Cesario, Lucas Malta Barbosa (2024)
Currently, competitiveness in the manufacturing sector demands the adoption of strategies that increase productivity and reduce waste. Lean Manufacturing, also known as Lean Production, is an approach aimed at optimizing production processes by eliminating non-value-added activities. In this context, Kaizen, which means "continuous improvement," is a fundamental philosophy of Lean Manufacturing that promotes incremental and constant improvements in operational processes. Accordingly, the general objective of this study was to analytically describe the Kaizen methodology in the Cabin Panel sector of a manufacturing company, aiming to increase productivity and operational efficiency. A case study was used as a method, where actions were implemented to balance the production line, reorganize the layout, apply ergonomic practices, and follow the principles of 5S. The results showed a 28% increase in operational efficiency, with significant reductions in cycle time and improvements in occupational safety and health, highlighting the effectiveness of the Kaizen methodology in transforming the manufacturing environment.